2017
DOI: 10.1152/ajprenal.00639.2016
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between renal endothelin and purinergic signaling systems

Abstract: Alterations in extracellular fluid volume regulation and sodium balance may result in the development and maintenance of salt-dependent hypertension, a major risk factor for cardiovascular disease. Numerous pathways contribute to the regulation of sodium excretion and blood pressure, including endothelin and purinergic signaling. Increasing evidence suggests a link between purinergic receptor activation and endothelin production within the renal collecting duct as a means of promoting natriuresis. A better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Previous studies in our laboratory revealed that angiotensin II could induce a rapid release of ATP in the isolated kidney, a response that was strongly enhanced in Dahl salt‐sensitive rats fed a high‐salt diet . Another mechanism that may stimulate ATP release and sodium excretion in response to an increase of RPP could be the proposed crosstalk between purinergic and endothelin signaling . Consistent with this, ATP release and P2 receptor stimulation were shown to be upstream events of the flow‐induced increases in endothelin expression and activity in the CCDs both of which play significant roles in the regulation of ENaC activity …”
Section: Discussionsupporting
confidence: 69%
“…Previous studies in our laboratory revealed that angiotensin II could induce a rapid release of ATP in the isolated kidney, a response that was strongly enhanced in Dahl salt‐sensitive rats fed a high‐salt diet . Another mechanism that may stimulate ATP release and sodium excretion in response to an increase of RPP could be the proposed crosstalk between purinergic and endothelin signaling . Consistent with this, ATP release and P2 receptor stimulation were shown to be upstream events of the flow‐induced increases in endothelin expression and activity in the CCDs both of which play significant roles in the regulation of ENaC activity …”
Section: Discussionsupporting
confidence: 69%
“…Consequently, P2 receptor-dependent effects in the upstream vasculature could have profound effects on renal medullary hemodynamics and tubular function. Intramedullary infusion of UTP can increase sodium excretion, possibly by activating P2Y 2/4 receptors (171,172). This natriuretic response was prevented by P2 receptor blockade with suramin, or by combined endothelin A/endothelin B receptor blockade, suggesting a novel endothelin and P2 receptor interaction (see sects.…”
Section: Extracellular Nucleotides/p2 Receptors and Medullary Blood Flowmentioning
confidence: 96%
“…Via the A1 receptor, adenosine plays a critical role in constricting the afferent arteriole as part of the tubuloglomerular feedback (TGF) system (57). The integrative nature of renal regulatory systems is a fundamental tenet of renal physiologists and includes, among other examples, the intersection of renal purinergic and endothelin systems and their effects on sodium excretion (58). Endothelin is a vasoconstrictor involved in regulating renal blood flow and sodium transport (59,60).…”
Section: Introductionmentioning
confidence: 99%